Application of video materials in Foreign Language Teaching - Fatieieva, V. H.; Sharapova, V. V.; Фатєєва, В. Г.; Шарапова, В. В. (My University, 2015)
The main aspects of application of video materials in foreign language teaching have been defined. The active applying of video forms is the important mean of communicative oriented method in the process of foreign language teaching. The examples of implementation of audio-visual means in class and extra-curriculum activities have been given
Застосування відеоматеріалів у процесі викладання іноземної мови
Fatieieva, V. H. Application of video materials in Foreign Language Teaching / V. H. Fatieieva, V. V. Sharapova // Гуманіт. вісн. НУК. – Миколаїв : НУК, 2015. – Вип. 8. – С. 44–46.
Keywords: video materials; the process of Foreign Language Teaching (FLT); extra-curriculum activity; communicative method; видеоматериалы; процесс обучения иностранному языку; внеаудиторные занятия; коммуникативный метод